(untitled) (Computer systems and information technologies, 2020)
In this paper, the actuality and importance of the process of supporting the decision-making about the possibility of donation based on the civil law grounds are proved. This realized process will help to decide about the possibility or impossibility of donation, in any case, taking into account all existing civil law grounds. A review of the literature was conducted. It proved that the known information systems in the field of donation and transplantology don’t propose the method of supporting the decision-making about the possibility of donation based on the civil law grounds. The review of the civil law grounds of donation in Ukraine was conducted. Production rules and method of supporting the decision-making about the possibility of donation based on civil law grounds has been first time developed. This method helps to the transplantation clinic staff to correctly form the Register of donors (living donors and posthumous donors), taking into account all current civil law grounds. The developed method standardizes the procedure of including donors in the Register, minimizing the impact of subjectivism and the human factor herewith. Thus, the developed method of supporting the decision-making about the possibility of donation minimizes the damage that the whole medical transplantation system may suffer and leverages the occurrence for its improvement. Experiment has shown that the developed method is workable and effective in determining the possibility of donation based on all currently existing civil law grounds in the complex. The perspective direction of the future authors’ work is the design and development of the subsystem for supporting the decision-making about the possibility of donationn– on the basis of the production rules and method of support of making the decision about donation possibility on the basis of civil law grounds, which are developed in this paper.